A Thorough Insight to Techniques for Performance Evaluation in Biological Sensors - Subhas Meti; V G Sangam (Institute of Advanced Engineering and Science, 2016)
The biological sensor has played a significant and contributory role in the area of medical science and healthcare industry. Owing to critical healthcare usage, it is essential that such type of sensors should be highly robust, sustainable under the adverse condition and highly fault tolerant against any forms of possible system failure in future. A massive amount of research work has been done in the area of the sensor network. However, works done in biological sensors are quite less in number. Hence, this manuscript highlights all the significant research work towards the line of discussion for evaluating the effective in the techniques for performance evaluation of biological sensor. The study finally explores the problems and discusses it under research gap. Finally, the manuscript gives highlights of the future direction of the work to solve the research gap explored from the proposed review of the existing system.